Effects of low-intensity pulsed ultrasound on wound healing in corneas of dogs following keratoplasty - Vicenti, F. A M [UNESP]; Laus, J. L. [UNESP]; Costa Neto, J. M.; Talieri, I. C. [UNESP]; Campos, C. F. [UNESP]; Jorge, A. T. [UNESP]; Ferreira, A. L.; Fantinatti, A. P. [UNESP] (Wiley, 2003)
The effects of low-intensity pulsed ultrasound on wound healing were evaluated at the graft-cornea transition in dogs following lamellar keratoplasty using tunica vaginalis preserved in 98% glycerin. Twenty-one dogs were subdivided into three groups of seven animals. The first group (W/US) received daily treatment of low-intensity pulsed ultrasound (20 mW/cm 2) for 15 min for the first 10 days post surgery. The second group (N/US) was submitted to the same procedure but with the ultrasound apparatus turned off. The third group, the control (CO), underwent the surgical procedure only. The animals were clinically evaluated during the initial (1-15 days), intermediate (16-30 days) and late (31-120 days) postoperative period. The corneas were evaluated by light microscopy at 1, 3, 7, 15, 30, 60 and 120 days after surgery. Clinically, there were no differences which would promote an advantage to any of the treatments. Light microscopy, however, revealed more extensive vascularization and more advanced wound healing in the W/US group, as well as a tendency towards early graft incorporation. Based on the present results, low-intensity pulsed ultrasound shows advantages, especially in situations where trophic support is a mandatory condition, facilitating better graft incorporation and rapid recovery of stromal organization.
Keywords: Corneal healing; Dogs; Keratoplasty; Tunica vaginalis; Ultrasound; glycerol; animal cell; animal tissue; controlled study; cornea injury; cornea transplantation; dog; evaluation; female; keratoplasty; lamellar body; low intensity ultrasound; male; microscopy; nonhuman; postoperative complication; postoperative period; stroma; tissue preservation; tunica vaginalis; ultrasound therapy; vascularization; wound healing; Animals; Cornea; Corneal Transplantation; Female; Male; Treatment Outcome; Ultrasonic Therapy; Wound Healing; Animalia; Canis familiaris